2006
DOI: 10.1021/bp0502680
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Expression of a Soluble Functional Antimicrobial Peptide, Human β-Defensin 2, in Escherichia coli

Abstract: In this work, taking human beta-defensin-2 (HBD2) as a demonstrative molecule, the strategies for high efficient production of functional human beta-defensins in E. coli were studied. Fusion mature HBD2 (TrxA-mHBD2) showed high solubility and productivity without the need for lowering the cultivation temperature. The solubility of target fusion protein could attain 81.3% even at 37 degrees C with a volumetric productivity as high as 235 mg/L in a rich medium MBL at the same temperature and reached 346 mg/L at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 20 publications
3
25
1
Order By: Relevance
“…In contrast to earlier reports about defensin production in E. coli K-12 strains (Huang et al, 2006;Pazgier and Lubkowski, 2006;Xu et al, 2006), this study reports for the first time the production of active HBD2 defensin in a probiotic E. coli strain (Nissle 1917), which is licensed as a drug for the treatment of patients suffering from e.g. diarrhea or ulcerative colitis.…”
Section: Listeria Monocytogenescontrasting
confidence: 59%
See 1 more Smart Citation
“…In contrast to earlier reports about defensin production in E. coli K-12 strains (Huang et al, 2006;Pazgier and Lubkowski, 2006;Xu et al, 2006), this study reports for the first time the production of active HBD2 defensin in a probiotic E. coli strain (Nissle 1917), which is licensed as a drug for the treatment of patients suffering from e.g. diarrhea or ulcerative colitis.…”
Section: Listeria Monocytogenescontrasting
confidence: 59%
“…It has been reported that a fusion expression system with thioredoxin (TrxA) resulted in an increased yield of soluble products (LaVallie et al 2000). This has been observed for HBD2 and HBD3 (Huang et al, 2006;Xu et al, 2006). …”
supporting
confidence: 67%
“…In addition to the cultivation temperature, the type of fusion protein utilized affected the yield of soluble HPV16 L1 production in E. coli. Our observation of the relatively lower yield of soluble HPV16 L1 upon fusion with GST is consistent with the previous findings of other groups, who reported a soluble GST-HPV16 L1 yields of less than 50% in E. coli [6,20]. Consistent with our findings, the MBP fusion tag was reported to be a more efficient solubilizing partner than GST for a set of proteins [21,22].…”
Section: Discussionsupporting
confidence: 93%
“…HBD-1 was cleaved from the fusion by protease 4 and the peptide was found to be active. Chen and colleagues have been improving the expression of HBD-2 for years [82,83]. They found that tandem expression and codon optimization could improve the expression level of the peptide.…”
Section: Peptide Productionmentioning
confidence: 99%